2022
DOI: 10.3389/fimmu.2022.753570
|View full text |Cite
|
Sign up to set email alerts
|

Determining Sex-Based Differences in Inflammatory Response in an Experimental Traumatic Brain Injury Model

Abstract: IntroductionTraumatic brain injury is a leading cause of injury-related death and morbidity. Multiple clinical and pre-clinical studies have reported various results regarding sex-based differences in TBI. Our accepted rodent model of traumatic brain injury was used to identify sex-based differences in the pathological features of TBI.MethodsMale and female Sprague-Dawley rats were subjected to either controlled-cortical impact (CCI) or sham injury; brain tissue was harvested at different time intervals depend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Additionally, our study cohorts were predominantly male. While a recent study in rodents found no sex-based differences in various pathological features of TBI including splenocyte cell proliferation, activation of microglia, and inflammatory cytokine production at 6 h post-injury 58 , future multi-center studies in diverse cohorts of TBI patients remain necessary to confirm this equivalence. We also note that, in addition to TBI, psychiatric and neurological factors (e.g., PTSD) can have an impact on the systemic stress response and need to be considered in future studies.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, our study cohorts were predominantly male. While a recent study in rodents found no sex-based differences in various pathological features of TBI including splenocyte cell proliferation, activation of microglia, and inflammatory cytokine production at 6 h post-injury 58 , future multi-center studies in diverse cohorts of TBI patients remain necessary to confirm this equivalence. We also note that, in addition to TBI, psychiatric and neurological factors (e.g., PTSD) can have an impact on the systemic stress response and need to be considered in future studies.…”
Section: Discussionmentioning
confidence: 90%
“…The pathophysiologic mechanisms underlying primary and secondary injury following TBI are likely more similar than different males and females, however, some differences are known to exist between males and females in TBI. In preclinical models of TBI, female animals have demonstrated decreased neuroinflammation, including reductions in reactive microglia and infiltrating peripheral immune cells [ 136 , 137 ], decreased BBB disruption [ 138 ], and decreased oxidative stress [ 139 ]. While the mechanistic differences in TBI pathophysiology are complex and still under investigation, the effect of female sex steroids, including estrogen and progesterone, has been suggested as a key underlying driver for these observed differences [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…The male rats were randomly divided into three groups, and each group included 14 rats. TBI was generated in rats by using the CCI model [ 21 , 39 , 40 ]. The details were as follows: (1) control group, no operated group (only opened 10 mm median linear incision was then sutured under anesthesia); (2) acute TBI, rats were sacrificed at 24 h after TBI; (3) chronic TBI, rats were sacrificed 30 days after TBI.…”
Section: Methodsmentioning
confidence: 99%
“…The CCI techniques, parameters, and postoperative care have all been thoroughly reported previously [ 21 , 39 , 40 ]. Rats were sedated with isoflurane (2.0–2.5 percent in 100% O 2 , 2.0 mL/min flow rate) and put in a stereotaxic frame with the head in a horizontal plane about the interaural line.…”
Section: Methodsmentioning
confidence: 99%